Analisis Kepadatan Hunian terhadap Angka Bakteri Udara dalam Rumah Di Sekitar TPA Sampah untuk Mencegah Terjadinya Penyakit Infeksi Pernafasan - Fithri, Nayla Kamilia (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2021)
Infectious diseases can be caused by biological agent such as bacteria, viruses or parasites which can spreadthrough air, water, soil, food and others. Sources of air pollutants can come from indoors or outdoors. One ofthe factors that can increase air pollution so that it affect indoor air quality is the density of the occupancy. Theresearch objective was to determine the relationship between the occupancy density variable and the quality ofair biology, namely the number of bacteria in the house around Piyungan Disposal Site, Bantul Regency, DIY.The method used in this research is to use a descriptive analytical survey research type with a cross-sectionalapproach to determine the relationship between occupancy density and the number of airborne bacteria in thehouse around TPAS. The research subjects were residents' houses around Disposal Site with a total sample of 39houses, with proposional random sampling technique. The results of the bivariate analysis with T-testIndependent showed a significant relationship between occupancy density (p-value = 0.016; coefficient = 2.11)and the number of airborne bacteria in the house. The conclusion in this study is that there is a relationshipbetween occupancy density and the number of airborne bacteria in the house, so it is hoped that the communitywill improve the physical condition of the house and the local government to improve the layout of landfills atleast 2 km from the settlement as well as planting trees to filter pollutant particles into the area. House.